Ekonomi Islam dan Peradaban: Analisis Mudharabah Sebagai Elemen Ekonomi Tolok Ukur Peradaban - Kumara Adji Kusuma; Abdul Hadi (Universitas Muhammadiyah Sidoarjo, 2016)
One of the main factors making up the basis of civilization or Madani society or civil society, which is also part of the social capital, is the confidence (trust) both horizontally and verticallyamong individuals between individuals and institutions so as to create an effective partnership. Islamic Economics is an economic system based on Islamic principles. Inside there is a contract ofMudharabah contract based on the belief that investors give full trust to capital manager with the agreement of the losses in the initial contract. In this study concluded that the higher the level of consumption in society Mudharabah contract is higher level then the level of civilization of society. This is because Mudharabah is directly proportional to the level of public confidence. This study uses library research both from the perspective of historical and economic, using critical-descriptive.